Rancang Bangun Sistem Informasi Manajemen Asset Berbasis Web Dengan Metode Waterfall - Tarigan, Satria; Supina Batubara (Jurnal Nasional Teknologi Komputer, 2024)
This research is an effort to design and build a web-based Asset Management Information System (SIMA) by applying the Waterfall Method. SIMA is an important component in managing an organization's assets, including the efficient procurement, maintenance and monitoring of assets. The Waterfall method was chosen because it has a systematic and structured approach, starting from the needs analysis stage to the implementation and system maintenance stages. The aim of this research is to optimize the asset management process by integrating web technology so that it can provide real-time and efficient access to information. This is expected to have a positive impact on more effective and measurable asset management in various industrial sectors. This research will focus on the key steps in developing a web-based SIMA using the Waterfall Method. The first stage is requirements analysis, where the functional and non-functional requirements of SIMA will be identified in detail. Next, system design will be carried out based on the results of the analysis, including designing the user interface and database structure. The implementation phase will change the system design into program codes that can run, followed by the testing phase to ensure the quality and performance of the system. Finally, the system will be fully implemented and maintained according to needs and changes that occur. Thus, it is hoped that this research can make a significant contribution in increasing the efficiency and effectiveness of asset management through the use of appropriate and structured information technology..